The complete chloroplast genome sequence of Pinus cembra L. (Pinaceae). Issue 2 (3rd July 2019) - Schott, Thomas; Schroeder, Hilke; Schöning-Stierand, Katrin; Kersten, Birgit
Abstract: The Swiss pine ( Pinus cembra ) is a montane tree in Central Europe and, therefore, known for its hardiness against severe winter colds. The seeds are harvested and eaten as pine nuts. We assembled and characterized the complete chloroplast genome of P. cembra to serve as a valuable resource in future genetic studies. The complete plastome sequence is 116, 609 bp in length and contains 113 genes including 79 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. A phylogenetic analysis of 34 Pinus plastome sequences shows that Pinus sibirica is the nearest relative to P. cembra and that there is a distinct clustering together with the other members of the section Quinquefoliae.